1922 Mass. Acts 563 - (:unkn) unknown (My University, 1922)
Ch. 485, An Act Relative to the Sale and Carrying of Firearms, ch. 485, § 8 (amending § 130): Prohibited the sale or furnishing of firearms, air guns, or dangerous weapons to minors under age 15 or noncitizens without a permit to carry firearms; violators subject to fine. Law does not apply to instructors furnishing military weapons to pupils for instruction or drill.
Keywords: TRANSFER - DANGEROUS PERSONS; TRANSFER - MINORS